Werewolf: the true story of an extraordinary police dog - Hedges, David Alton (David Alton Hedges, 2021)
WEREWOLF: The True Story of an Extraordinary Police Dog is the raw, first-hand account of the life of a police K9 named “Brag” and his cop partner. When they first meet, Brag shows no interest in human attachment and his handler is wary of caring too much for a dog whose life he must risk every night. But as the dangerous manhunts push both to their mental and physical limits, the two develop an unbreakable bond that blurs the line between human and canine. Anyone who has ever loved a dog will embrace this heartfelt story of courage and loyalty!